The effects of long-term administration of tadalafil on STZ-induced diabetic rats with erectile dysfunction via a local antioxidative mechanism - Chen, Yun (Nature Publishing Group, 2012)
Type 5 phosphodiesterase inhibitors (PDE5Is) are well known being effective via the nitric oxide and cyclic guanosine monophosphate (NO–cGMP) pathway and are widely used in the treatment of diabetic erectile dysfunction (ED). However, it is unclear whether other pathways may be involved in the treatment of diabetic ED with PDE5Is. The purpose of this study was to clarify the role of antioxidants in diabetic ED treatment through the long-term administration of PDE5Is. Three groups of Sprague–Dawley rats were utilized: Group N, the normal control; Group D, streptozotocin (STZ)-induced diabetic rats as a control; and Group D+T, STZ-induced diabetic rats who received oral administration of tadalafil for 8 weeks. Erectile function was assessed by intracavernous pressure (ICP) and mean arterial pressure (MAP) during electrical stimulation of the cavernous nerve before euthanasia. The levels of malondialdehyde (MDA), superoxide dismutase (SOD) and mitochondrial membrane potential (MMP) of cavernous tissue were assessed by biochemical analysis. The morphology of mitochondria was observed by electron microscopy. The ICP/MAP ratio was higher in Group D+T than in Group D (P<0.05). The levels of MDA decreased and the activities of SOD increased in Group D+T in comparison with Group D (P<0.05). The mitochondrial membrane potential level of cavernous tissue in diabetic rats was partially recovered by tadalafil treatment for 8 weeks. The morphology changes of mitochondria were also remarkably ameliorated in Group D+T. Collectively, the long-term administration of tadalafil in diabetic rats partially reduced oxidative stress lesions of the penis via a local antioxidative stress pathway. Long-term dosages of tadalafil given once daily beginning soon after the onset of diabetes may aid in preventing rats from developing diabetic ED.